Assessment of Exercise Capacity in Children with Type 1 Diabetes in the Cooper Running Test - Michalak, Arkadiusz; Gawrecki, Andrzej; Gałczyński, Szymon; Nowaczyk, Jędrzej; Mianowska, Beata; Zozulinska-Ziolkiewicz, Dorota; Szadkowska, Agnieszka (International Journal of Sports Medicine, 2019)
Regular physical activity increases lifespan for those with type 1 diabetes. However, disease-related barriers may deter children from exercise and affect their fitness. This study examined the safety of the Cooper test concerning diabetes-related acute complications in children with type 1 diabetes and their fitness. Blood glucose was recorded before and 0, 30, 60 min after the test. The covered distances were transformed to z-scores based on the national charts. Body mass index, body fat percentage and glycated hemoglobin were measured. The run was completed by 80 individuals (45% boys, age 13.6±2.1 years; diabetes duration 6.3±3.5 years). During the follow-up 11 children reached glucose alert values (3–3.9 mmol/L), 3 presented clinically significant hypoglycemia (<3 mmol/L), none experienced severe hypoglycemia. The covered distance was 1914±298 m, not significantly different from the reference population (z-score −0.12±0.71 vs 0, p=0.12). The study participants were more overweight than general pediatric population in terms of body mass index (z-score 0.48±0.94 vs 0, p<0.001) and body fat percentage (z-score: 0.37±0.85 vs 0, p<0.001). In conclusion, the Cooper test can be safely used in children with diabetes to assess their physical capacity. Youth with type 1 diabetes present fitness similar to healthy children but exhibit increased body mass index and adiposity.
Keywords: type 1 diabetes; children; Cooper test; physical capacity; percentile charts